Economic growth across space and time: subprovincial evidence from mainland China - Declan Curran; Michael Funke; Jue Wang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2007)
This paper considers the persistent differences in economic performance across Chinese regions. We introduce a new county- and city-level dataset that spans all of mainland China and provides a detailed view of Chinese regional growth over the period 1997-2005. Non-parametric kernel density estimation is employed to establish the cross-sectional GDP per capita distribution, and the distributional dynamics are investigated using the probability matrix technique and associated stochastic kernel estimator. A set of explanatory variables is then introduced, and several regressions are run to test for conditional ß- convergence and to pinpoint influential factors for economic growth across counties and cities.
URN:NBN:fi:bof-201408072005
Keywords: O11; R11; 330; Regional Economic Growth; China